Nothing but blackened teeth eaudiobook - Khaw, Cassandra (Macmillan Audio, 2021)
Cassandra Khaw's Nothing But Blackened Teeth is a gorgeously creepy haunted house tale, steeped in Japanese folklore and full of devastating twists. A Heian-era mansion stands abandoned, its foundations resting on the bones of a bride and its walls packed with the remains of the girls sacrificed to keep her company. It's the perfect venue for a group of thrill-seeking friends, brought back together to celebrate a wedding. A night of food, drinks, and games quickly spirals into a nightmare as secrets get dragged out and relationships are tested. But the house has secrets too. Lurking in the shadows is the ghost bride with a black smile and a hungry heart. And she gets lonely down there in the dirt. Effortlessly turning the classic haunted house story on its head, Nothing but Blackened Teeth is a sharp and devastating exploration of grief, the parasitic nature of relationships, and the consequences of our actions. A Macmillan Audio production from Tor Nightfire